A Study of IPS Teachers Facing The Challenges of Diffusion of Learning Innovations Based on The Era Of Society 5.0 - Maftuchin, Maftuchin; Aransyah, Ade; Kusuma, Febra Anjar (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
The era of society 5.0 is a continuation of the industrial revolution 4.0 era which emphasizes humanism in solving social problems including education by integrating virtual and reality. This research aims to analyze government policies on teacher development in the era of society 5.0. Basically learning and learning is a change in a person’s behavior in achieving a goal. Social studies is a discipline that studies social life. Not only as social science. This research is a study of the challenges of social studies teachers in the diffusion of learning innovations based on ERA SCOETY 5.0. This research uses Systematic Literature Review (SLR). The SLR method is used to identify, review, evaluate and interpret all available research with the topic area of the phenomenon of interest, with specific relevant research questions. It is important to keep in mind that Society 5.0 is a constantly evolving idea, and how it is applied may vary in different countries and environments. When one analyzes a learning system that fits Society 5.0, they must consider the social, economic, and technological changes taking place in modern society. Teachers as the driving force in the education sector, are expected to be able to develop learning and learning processes that are in accordance with the characteristics of the learners, not just developing the challenges of social studies teachers in the future will be more complex and must be ready for a future based on scoety 5.0 in terms of learning and learning